PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SCRATCH PADA MATERI OPERASI HITUNG BILANGAN BULAT KELAS VII SMP - Kemala Puspita Dewi; Abd. Basir Abbas; Tri Widyasari; Petrus Fendiyanto (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This development research is based on students’ limited understanding of integer arithmetic operations, particularly negative numbers, as well as the lack of interactive learning media in the learning process. This study aims to examine the process of developing Scratch-based learning media for integer arithmetic operations and to determine the validity and practicality of the developed media. This study employs the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The instruments used include validation sheets for subject matter experts and media experts, as well as a practicality questionnaire for students. Data collection techniques were conducted through interviews, observations, and questionnaires. The results of the study indicate that the learning media was developed through stages of needs analysis, curriculum analysis, and technology analysis; media and instrument design; product creation in the form of Scratch-based interactive media containing content, practice problems, and educational games; validation; revision; and finally, pilot testing with students. The learning media was deemed highly valid by subject matter experts (87.33%) and by media experts (97.04%), and highly practical based on student responses (91.49%). Thus, the Scratch-based learning media developed was deemed suitable and highly practical for use in teaching mathematics on integer arithmetic for 7th-grade junior high school students.